2018
DOI: 10.21831/jpv.v8i3.20775
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of students industrial training courses implementation at higher education

Abstract: This article aims to reveal the factual basis regarding the implementation of Students Industrial Training (SIT) course by the bachelor’s degree students of Hospitality Management Department from the Faculty of Tourism and Hospitality at the University. The methodology used in this study is mixed method with CSE-UCLA evaluation model. The informants in this study were 35 hospitality management students who were graduated in 2015, the SIT Coordinators, Heads of Tourism Departments, and Supervisors, Managers, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
0
0
1
Order By: Relevance
“…Training in the industry includes bringing students towards learning that adheres to the principles of CTL. Therefore the results of this study support the results of the study of Ambiyar, Yulastri, Putri, & Wulansari (2018) which concluded that Industrial training can improve student knowledge, work skills, and English language skills, and enhance the role of supervisors and instructors/industrial supervisors and provide solutions for students to overcome the problems they face. Furthermore, this training program is needed to improve the quality of tourism facilities and infrastructure into the hospitality industry and improve the attitude of students in conducting industrial training courses.…”
Section: Research Results and Discussionsupporting
confidence: 82%
“…Training in the industry includes bringing students towards learning that adheres to the principles of CTL. Therefore the results of this study support the results of the study of Ambiyar, Yulastri, Putri, & Wulansari (2018) which concluded that Industrial training can improve student knowledge, work skills, and English language skills, and enhance the role of supervisors and instructors/industrial supervisors and provide solutions for students to overcome the problems they face. Furthermore, this training program is needed to improve the quality of tourism facilities and infrastructure into the hospitality industry and improve the attitude of students in conducting industrial training courses.…”
Section: Research Results and Discussionsupporting
confidence: 82%
“…Menurut Rossi, et all (dalam (Ambiyar, Yulastri, Putri, & Wulansari, 2018) : "Evaluation research is the systematic application of social research proce dures in assessing the conceptualization and design, implementation, and utility of social intervention programs". Berdasarkan definisi tersebut, penelitian evaluasi adalah aplikasi secara sistematis dari prosedur-prosedur penelitian sosial yang dapat menilai konsep dan rancangan, pelaksanaan, serta kegunaan dari program intervensi sosial.…”
Section: Pendahuluanunclassified